Numerical Study of Performance Enhancement of Phase Change Material (PCM) Thermal Energy Storage (TES) System by Using Nanoparticles - Hussain, Ebtehal S.; Hussain, Ihsan Y. (Al-Nahrain Journal for Engineering Sciences, 2025)
Improvements in the thermo-physical properties of Phase Change Materials (PCM) caused by nanoparticle dissipation are critical for a wide range of technologies. The current study describes numerically the investigation of the charging and discharging process of paraffin wax dispersed with different concentrations (1%, 3%, 5%, 7%, and 10% ) of Alumina nanoparticles (Al2O3), in a Single Thermal Energy Storage (STES) system. For this study, a time-dependent, two-dimensional simulation of the solidification and melting process was performed numerically for different velocities. The study is realized using the CFD ANSYS FLUENT software package (Version 18) that employs the phase-change phenomenon using the enthalpy technique. The results show that adding alumina nanoparticles to paraffin wax reduces the melting and solidification process, and raising nanoparticle concentration accelerated the melting and solidification process even more when compared to pure paraffin wax. The greatest improvement was obtained with the maximum concentration of nanoparticles with total time saving between (12% - 11.76% ) in the charging process and between ( 15.71% - 19.60% ) in the discharging process depending on velocity. Furthermore, other important findings were that the presence of nanoparticles makes a little effect in the early stages of the solidification and melting processes, but as time passes, the rate of solidification and melting rises. Comparison with previous works gave good agreement of about 34%.